JUDICIAL ANALYSIS OF THE PROTECTION AND PRESERVATION OF TRADITIONAL CULTURAL EXPRESSIONS IN PURWOREJO REGENCY - Bagus Anwar Hidayatulloh; Said Munawar; Muhammad Rusdi; Hartanto (Media Inovasi Pendidikan dan Publikasi, 2024)
The Indonesian state has a firm and constitutional obligation to advance national culture as mandated in Article 32, paragraph (1) of the 1945 Constitution. This article guarantees the freedom of the community to preserve and develop cultural values. Indonesian culture, reflecting the noble values of the nation, must be embraced by all citizens to strengthen national identity, enhance dignity, and reinforce unity to achieve the nation's future goals. The preamble of the 1945 Constitution of the Republic of Indonesia outlines the national goals of protecting all Indonesians and their homeland, promoting general welfare, educating the nation's life, and participating in maintaining world order based on freedom, eternal peace, and social justice. The diversity of ethnic groups, customs, languages, local knowledge and technology, traditions, local wisdom, and arts are valuable cultural heritages that shape the nation's identity amid global development. According to various articles in the 1945 Constitution of the Republic of Indonesia, the country possesses extraordinary artistic and cultural wealth that must be protected. Local governments, as the forefront of governance, have an obligation to preserve culture to strengthen the nation's identity. Purworejo Regency, with its rich local traditions, has the responsibility to preserve regional cultural expressions through protection, development, utilization, coaching, and cultural supervision. Copyright protection of traditional art works is considered an economic asset and a national identity. The Purworejo Regional House of Representatives (DPRD) has taken the initiative to draft regional regulations to protect and preserve traditional cultural expressions, demonstrating the local government's commitment to safeguarding cultural heritage and promoting the development of local cultural wealth for the welfare of the community and regional advancement.